Structural diversity in manganese, iron and cobalt complexes of the ditopic 1,2- bis(2,2’-bipyridyl-6-yl)ethyne ligand and observation of epoxidation and catalase activity of manganese compounds - Madhu, Vedichi; Ekambaram, Balaraman; Shimon, Linda J. W.; Diskin, Yael; Leitus, Gregory; Neumann, Ronny (Royal Society of Chemistry, 2010)
A ditopic 1,2-bis(2,2′-bipyridyl-6-yl)ethyne ligand, L, has been synthesized for the first time by consecutive Suzuki and Sonogashira coupling reactions either in a one- or two-step synthesis. Coordination of L with some first-row transition metals, Fe, Mn and Co showed a very rich structural diversity that can be obtained with this ligand. Reaction of L with MnII(OAc)2 yielded a dimanganese(II) complex, [Mn2L(μ-OAc)3]PF6, (1) where the two somewhat inequivalent trigonal-bipyramidal Mn atoms separated by 3.381 Å are bridged by L and three acetate moieties. A similar reaction of L with MnIII(OAc)3 yielded a very different dimanganese complex [Mn2L′(OH)(OAc)2(DMF)2]PF6·DMF (2) where L′ is a E-1,2-bis(2,2′-bipyridyl-6-yl)ethene fragment that was formed in situ. The L′ ligand bridges between the two Mn centers, despite its trans configuration, which leads to a very strained ethene bridging moiety. The Mn atoms are also bridged by two acetate ligands and a hydroxy group that bridges between the Mn atoms and the ethene fragment; DMF completes the octahedral coordination around each Mn atom which are separated by 3.351 Å. A comproportionation reaction of L with MnII(OAc)2 and n-Bu4NMnO4 yielded a tetramanganese compound, [Mn4(μ3-O)2(OAc)4(H2O)2L2](PF6)2·2CH3CN (3). Compound 3 has a dimer of dimers structure of the tetranuclear Mn core that consists of binuclear [Mn2O(OAc)2L]+ fragment and a PF6 anion. BVS calculations indicate that 3 is a mixed-valent 2MnII plus 2MnIII compound where two [MnII2O(OAc)2L]+ fragments are held together by MnIII–O inter-fragment linkers which have a distorted octahedral geometry. The Mn atoms in the [Mn2O(OAc)2L]+ fragments have a capped square-pyramid configuration where an aqua ligand is capped on one of the faces. Although the aqua ligand is well within a bonding distance to a carbon atom of the proximal ethyne bridge, there does not appear to be an oxygen–carbon bond formation, rather the ligand is constrained in this position, as deduced by the observation that the bond lengths and angles of the ligand are essentially the same as those for the free ligand, L. Reaction of L with perchlorate or triflate salts of Fe(II), Mn(II) and Co(II) in dry acetonitrile yielded binuclear triple helicate structures (2[thin space (1/6-em)]:[thin space (1/6-em)]3 metal to L ratios) [Fe2L3](CF3SO3)4·CH3CN (4), [Mn2L3](ClO4)4·1.7CH3CN·1.65EtOEt (5) and [Co2L3](ClO4)4·2CH3CN·2EtOEt (6) where each M(II) center with a slightly distorted octahedral geometry is bridged by three of the ditopic ligands. The M–M distances varied; 5.961 Å (Mn), 6.233 Å (Co) 6.331 Å (Fe). Reaction of L with Co(ClO4)2·6H2O in wet acetonitrile yielded a dicobalto(III) compound, [Co2L′3(O)2](ClO4)2·H2O (7), with two types of L′ fragments; one bridging between the two Co centers and two non-bridging ligands, each bonded to a Co atom via one bipyridyl group where the other is non-bonding. The octahedral coordination sphere around each Co atom is completed by the formation of a cobalt–carbon bond from the two carbon atoms of the ethene moiety of the bridging ligand and by a hydroxy moiety that is also bonded to the ethene group of the non-bridging ligand. Reaction of L with Co(ClO4)2·6H2O in dry acetonitrile in the presence of Et3N yielded the tetracobalto(II) complex {[Co2L4(OH)4](ClO4)4}2 (8) with a unique twisted square configuration of cobalt ions with Co–Co distances of 3.938 to 4.131 Å. In addition to the L bridging ligand the Co atoms are linked by hydroxy moieties. Some preliminary catalytic studies showed that the Mn compounds 1 and 2 were active (high yield within 3 min) for alkene epoxidation with peracetic acid and hydrogen peroxide dismutation (catalase activity).

Electron-rich PNP- and PNN-type Ru(II) hydrido-borohydride complexes. synthesis, structure and catalytic activity towards dehydrogenation of alcohols and hydrogenation of esters - Zhang, Jing; Balaraman, Ekambaram; Leitus, Gregory; Milstein, David (Organometallics, 2011)
Electron-rich PNP- and PNN-type ruthenium(II) hydrido borohydride pincer complexes, [RuH(BH4)(tBu-PNP)] (tBu-PNP = (2,6-bis(di-tert-butylphosphinomethyl)pyridine) (5) and [RuH(BH4)(tBu-PNN)] (tBu-PNN = 2-di-tert-butylphosphinomethyl-6-diethylaminomethylpyridine) (6), were prepared from their corresponding N2-bridged dinuclear Ru(II) complexes [(tBu-PNP)RuCl2]2(μ-N2) (3) and [(tBu-PNN)RuCl2]2(μ-N2) (4), respectively. The X-ray structure of 5 reveals a BH4– anion η2 coordinated to ruthenium through two bridging hydrides. A variable-temperature 1H NMR study of 6 exhibits interesting fluxional behavior of the BH4– ligand. Similarly, the Ru(II) hydrido borohydride complex 9, in which the BH4– moiety is coordinated in a η1 bonding mode, was obtained by reaction of [RuCl2(PPh3)(iPr-PNP)] (iPr-PNP = 2,6-bis(diisopropylphosphinomethyl)pyridine) (8) with two equivalents of NaBH4 at room temperature. The hydrido borohydride pincer complexes 5, 6, and 9 catalyze the acceptorless dehydrogenative coupling of primary alcohols to esters and the dehydrogenation of secondary alcohols to the corresponding ketones, accompanied by evolution of hydrogen gas. The reactivity follows the order 6 > 9 > 5. With the hydrido borohydride complex 6 as catalyst, high yields (up to 98%) and high turnover numbers (TON ∼1000) were obtained in the dehydrogenation of primary alcohols under mild and neutral conditions. In addition, 6 effectively catalyzes the hydrogenation of nonactivated aromatic and aliphatic esters to the corresponding alcohols with TON ∼200 under a relatively mild pressure of dihydrogen and neutral and homogeneous conditions. Thus, an efficient homogeneous catalytic system for the dehydrogenation–hydrogenation reactions of alcohols is developed, which is relevant to the current interest in hydrogen storage.

New CNN-type ruthenium pincer NHC complexes. synthesis and catalytic activity. mild, efficient hydrogenation of esters - Fogler, Eran; Balaraman, Ekambaram; Ben-David, Yehoshoa; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2011)
New pincer ruthenium complexes (2–6) based on the new bipyridine-NHC ligand 1 were prepared and studied, resulting in an efficient catalytic hydrogenation of esters to the corresponding alcohols under mild conditions. Reaction of the ligand 1 with RuH(Cl)CO(PPh3)3, followed by reaction with one equivalent of the base KHMDS, gave the mixed phosphine-NHC complex 2, incorporating a C–H-activated bipyridine ligand. Complex 2 has an octahedral structure containing two phosphorus atoms trans to each other, a hydride trans to the NHC ligand, and CO trans to the C–H-activated carbon of the bipyridine ligand. Using the precursor complex Ru(p-cymene)Cl2(CO), reaction with 1 followed by treatment of the intermediate product with one equivalent of KHMDS resulted in formation of the dichloride pincer complexes 3a and 3b, which are in equilibrium, as indicated by variable-temperature 1H NMR. Complex 3a is an octahedral, neutral, and symmetric complex with the CO ligand positioned trans to the central pyridine group of the pincer ligand and the two chlorides trans to each other, as indicated by single-crystal X-ray diffraction. Complex 3b is cationic, with an outer-sphere chloride. Reaction of the NHC ligand 1 with LiHMDS at low temperature followed by addition of RuH(Cl)CO(PPh3)3 resulted in the mixed phosphine-NHC complex 4, which has an octahedral structure containing phosphorus trans to the hydride, a CO trans to the NHC ligand, and an outer-sphere chloride. Chloride substitution by BArF– gave the X-ray-characterized complex 5. Deprotonation of complex 4 with KHMDS resulted in formation of the dearomatized complex 6. The in situ prepared 6 (from complex 4 and an equivalent of base) is among the best catalysts known for the hydrogenation of nonactivated esters to the corresponding alcohols under mild conditions.

Catalytic transformation of alcohols to carboxylic acid salts and H2 using water as the oxygen atom source - Balaraman, Ekambaram; Khaskin, Eugene; Leitus, Gregory; Milstein, David (Nature Chemistry, 2013)
The oxidation of alcohols to carboxylic acids is an important industrial reaction used in the synthesis of bulk and fine chemicals. Most current processes are performed by making use of either stoichiometric amounts of toxic oxidizing agents or the use of pressurized dioxygen. Here, we describe an alternative dehydrogenative pathway effected by water and base with the concomitant generation of hydrogen gas. A homogeneous ruthenium complex catalyses the transformation of primary alcohols to carboxylic acid salts at low catalyst loadings (0.2 mol%) in basic aqueous solution. A consequence of this finding could be a safer and cleaner process for the synthesis of carboxylic acids and their derivatives at both laboratory and industrial scales.

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.

Synthesis, structures, and dearomatization by deprotonation of iron complexes featuring bipyridine-based PNN pincer ligands - Zell, Thomas; Langer, Robert; Iron, Mark A.; Konstantinovski, Leonid; Shimon, Linda J. W.; Diskin-Posner, Yael; Leitus, Gregory; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Inorganic Chemistry, 2013)
The synthesis and characterization of new iron pincer complexes bearing bipyridine-based PNN ligands is reported. Three phosphine-substituted pincer ligands, namely, the known tBu-PNN (6-((di-tert-butylphosphino)methyl)-2,2′-bipyridine) and the two new iPr-PNN (6-((di-iso-propylphosphino)methyl)-2,2′-bipyridine) and Ph-PNN (6-((diphenylphosphino)methyl)-2,2′-bipyridine) ligands were synthesized and studied in ligation reactions with iron(II) chloride and bromide. These reactions lead to the formation of two types of complexes: mono-chelated neutral complexes of the type [(R-PNN)Fe(X)2] and bis-chelated dicationic complexes of the type [(R-PNN)2Fe]2+. The complexes [(R-PNN)Fe(X)2] (1: R = tBu, X = Cl, 2: R = tBu, X = Br, 3: R = iPr, X = Cl, and 4: R = iPr, X = Br) are readily prepared from reactions of FeX2 with the free R-PNN ligand in a 1:1 ratio. Magnetic susceptibility measurements show that these complexes have a high-spin ground state (S = 2) at room temperature. Employing a 2-fold or higher excess of iPr-PNN, diamagnetic hexacoordinated dicationic complexes of the type [(iPr-PNN)2Fe](X)2 (5: X = Cl, and 6: X = Br) are formed. The reactions of Ph-PNN with FeX2 in a 1:1 ratio lead to similar complexes of the type [(Ph-PNN)2Fe](FeX4) (7: X = Cl, and 8: X = Br). Single crystal X-ray studies of 1, 2, 4, 6, and 8 do not indicate electron transfer from the FeII centers to the neutral bipyridine unit based on the determined bond lengths. Density functional theory (DFT) calculations were performed to compare the relative energies of the mono- and bis-chelated complexes. The doubly deprotonated complexes [(R-PNN*)2Fe] (9: R = iPr, and 10: R = Ph) were synthesized by reactions of the dicationic complexes 6 and 8 with KOtBu. The dearomatized nature of the central pyridine of the pincer ligand was established by X-ray diffraction analysis of single crystals of 10. Reactivity studies show that 9 and 10 have a slightly different behavior in protonation reactions.